Processing technologies for improved digestibility of milk proteins. (December 2021) - Bhat, Zuhaib F.; Morton, James D.; El-Din A. Bekhit, Alaa; Kumar, Sunil; Bhat, Hina F.
Abstract: Background: Milk and milk products often contribute a significant portion to the daily human diet and provide highly bioavailable animal proteins for maintenance and growth. Several processing technologies have the potential to affect the structural and functional properties of the milk proteins and can influence their fate in the gastrointestinal tract. Scope and approach: The present review examines the thermal and non-thermal processing technologies that affect the digestibility of milk proteins and influence the behaviour of milk proteins within gastrointestinal digestion environments. We reviewed papers that have been published in the last five years on different aspects of milk protein digestibility. Key findings and conclusions: Processing of milk and milk products can induce several modifications in the proteins that change their susceptibility to digestive enzymes in the gut. Several emerging nonthermal technologies, such as high-pressure, ultrasound, pulsed light, microfluidization and microfiltration, have been reported to induce protein structural changes which can cause denaturation, conformational changes and unfolding of the proteins, thereby increasing their susceptibility to enzymatic hydrolysis. Thermal processing technologies, such as ohmic heating, microwave and pasteurization, also have potential to induce protein structural and conformational changes which can affect their digestive behaviour during gastrointestinal digestion. Some of these processing technologies have been reported to increase the susceptibility of milk proteins that are otherwise resistant to gastric or intestinal digestion and can reduce the allergenicity of the milk proteins. The present review examines in detail the underlying mechanisms of how different thermal and non-thermal technologies mediate the digestibility of milk proteins. Expanding our understanding of the digestion of milk proteins has commercial potential and could increase opportunities for the application of milk proteins. Highlights: Emerging processing technologies improve digestibility of milk proteins. Both thermal and non-thermal processes have potential to affect digestibility of milk proteins. Processing conditions determine the overall impact on milk protein digestibility. Alterations in protein structure and microstructural changes are major underlying mechanisms.